Green Synthesis and Characterization of Reduced Graphene Oxide (RGO) using Sabdarriffa L extract and its Solubility Property. (November 2020) - Alshamsi, Hassan Abbas; Ali, Sura K.; Alwan Altaa, Salam H.
Abstract: In this work, a synthesis of reduced graphene oxide using Hibiscus Sabdarriffa L extract was investigated. This way is operationally easy and environmentally friendly at compared with the reduction methods of graphene oxide using chemical agents. The prepared GO and reduced GO were characterized by Raman spectroscopy, UV-vis spectroscopy, Fourier Transform-Infrared Spectroscopy (FTIR), X-ray diffraction (XRD), Scanning Electron Microscope (SEM), Transition Electronic Microscope (TEM), Atomic Force Microscopy (AFM), Brunauer-Emmett-Teller (BET), Photoluminescence (PL)and Thermogravimetric analysis (TGA) provide a good indication of the removal of oxygen-containing groups from GO and the formation of RGO.It is found that the graphene sheets possess a frizzy morphology consisting of a thin wrinkled paper-like structure, fewer layers and large specific surface area (506.6m 2 g −1 ) and good thermal stability. Measurements show that the use of a natural agent is more likely to reduce functional aggregates in the graphene oxide than hydrazine. Moreover, it is less toxic, less volatile and safer than others.